2019
DOI: 10.3390/socsci8030099
|View full text |Cite
|
Sign up to set email alerts
|

Transportation or Narrative Completion? Attentiveness during Binge-Watching Moderates Regret

Abstract: Extant results on the binge-watching outcomes have been mixed. This study sought to examine the crucial factor of attentiveness that might help to enhance viewer experience and mitigate post-binge regret, as well as differentiate the motivation of narrative transportation from narrative completion. While narrative transportation involves a viewer getting unconsciously swept away by the story, the motivation of narrative completion is a more self-aware, cognizant effort to progress through the story. A survey (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Such results seem to comply with research which implies that problematic binge-watching can be related to the regulation of negative emotions, impulsivity, loss of control and regret [7,8,38,50]. Furthermore, Tóth-Király et al [32] and Pittman and Steiner [33] imply that neuroticism is related to binge-watching and it is also a significant predictor of Internet addiction [36,51,52]. Another significant factor for all symptoms of problematic binge-watching, apart from Loss of control and neglect of duties, was low Agreeableness.…”
Section: Discussionsupporting
confidence: 77%
“…Such results seem to comply with research which implies that problematic binge-watching can be related to the regulation of negative emotions, impulsivity, loss of control and regret [7,8,38,50]. Furthermore, Tóth-Király et al [32] and Pittman and Steiner [33] imply that neuroticism is related to binge-watching and it is also a significant predictor of Internet addiction [36,51,52]. Another significant factor for all symptoms of problematic binge-watching, apart from Loss of control and neglect of duties, was low Agreeableness.…”
Section: Discussionsupporting
confidence: 77%
“…Consequently, the watching of several episodes of one series in a row has become a popular viewing pattern. Although no empiri-DOI: 10.1159/000506307 cally validated definition exists so far, several authors suggested watching > 2 episodes in one sitting as criterion for binge-watching [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, they found that when viewers consider narrative transportation important for binge-watching, attentive viewing produces the least amount of regret; when the importance of transportation was low, attention levels to content did not influence binge-watching regret. In view of the current study's data and Pittman and Steiner's (2019) cross-sectional survey results, there is an opportunity here for binge-watching research to expand Green and Brock's (2000;Green & Brock, 2002) transportation theory, by bringing in insights from psychological research on the intrinsic motivational forces that drive human behavior.…”
Section: Discussionmentioning
confidence: 90%
“…In that sense, results here suggest that engagement in binge-watching can fuel the development of an intrinsic motivation resulting from gratifications associated with long and frequent viewing sessions, to the point that binge-watching becomes a selfreinforcing behavior-a proposition advanced by Panda and Pandey (2017), but not yet tested empirically. Pittman and Steiner (2019) noted this possibility in a recent quantitative investigation of binge-watching. They interpreted correlational links between narrative transportation, attention and binge-watching regret as indicators that narrative transportation may motivate binge-watching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation